Material provision of bailiffs in Russian empire in the second half of the XIX century (based on materials of Penza region) - D V Boldyrev (RUDN Journal of Russian History, 2013)
The article analyses the system of bailiffs’ material provision in the 1860–1890s. It focuses on the core elements forming bailiffs’ salary and the reasons for remuneration of bailiffs for executing their duties. The article characterizes the financial responsibility of bailiffs in the form of deductions and levy of pledge when assuming the post. The author concludes that the system of bailiffs’ salaries at that period had not yet been developed as an effective set of measures and guarantees to protect a bailiff on the part of the State.